Demonstration of a novel apamin-insensitive calcium-activated K+ channel in mouse pancreatic B cells. - Ammälä, C; Bokvist, K; Larsson, O; Berggren, P; Rorsman, P (1993)
The whole-cell configuration of the patch-clamp technique was used to characterize the biophysical and pharmacological properties of an oscillating K(+)-current that can be induced by intracellular application of GTP[gamma S] in mouse pancreatic B cells (Ammälä et al. 1991). These K+ conductance changes are evoked by periodic increases in the cytoplasmic Ca2+ concentration ([Ca2+]i) and transiently repolarize the B cell, thus inhibiting action-potential firing and giving rise to a bursting pattern. GTP[gamma S]-evoked oscillations in K+ conductance were reversibly suppressed by a high (300 microM) concentration of carbamylcholine. By contrast, alpha 2-adrenoreceptor stimulation by 20 microM clonidine did not interfere with the oscillatory behaviour but evoked a small sustained outward current. At 0 mV membrane potential, the oscillating K(+)-current elicited by GTP[gamma S] was highly sensitive to extracellular tetraethylammonium (TEA; 70% block by 1 mM). The TEA-resistant component, which carried approximately 80% of the current at -40 mV, was affected neither by apamin (1 microM) nor by tolbutamide (500 microM). The current evoked by internal GTP[gamma S] was highly selective for K+, as demonstrated by a 51-mV change in the reversal potential for a sevenfold change in [K+]o. Stationary fluctuation analysis indicated a unitary conductance of 0.5 pS when measured with symmetric (approximately 140 mM) KCl solutions. The estimated single-channel conductance with physiological ionic gradients is 0.1 pS. The results indicate the existence of a novel Ca(2+)-gated K+ conductance in pancreatic B cells. Activation of this K+ current may contribute to the generation of the oscillatory electrical activity characterizing the B cell at intermediate glucose concentrations.